GP14 Adolescents use of metaphors to narrate their experience's of living with chronic kidney disease: an irish perspective. (June 2019) - O'Neill, Colleen; Casey, Briege; Lambert, Veronica; Awan, Atif
Abstract : Objective: Chronic Kidney Disease (CKD) is a debilitating lifelong condition, which can impact many aspects of a person's life. Experiencing CKD during adolescence is further complicated by the multitude of developmental changes that young people go through at this time period. There is limited research that examines the perspectives of adolescents living with CKD and how they make sense of their experiences. This poster presentation will display/illustrate how adolescents' use metaphors to narrate their experiences of living with Chronic Kidney Disease. These findings were identified from a qualitative narrative study examining Irish adolescents' embodied experience of living with CKD. Methods: A narrative study using an ethnographic approach was used in this study. Multiple methods were used to engage with five adolescents (10–17 years) living with CKD over an 18-month timeframe in both hospital and home settings. Data was collected from participants through participant observation, informal interviews and participatory methods i.e. body mapping. The collective stories of the adolescents were analysed using Riesman's approach to narrative analysis. Results: The findings of this study reveal that adolescents use visual and textual metaphors as a strategy for communicating the complexities of living with CKD. Within their narratives, adolescents, used scientific metaphors (CKD as a 'black hole' and ' atom '), journey metaphors ( Orbiting ) and supernatural metaphors ( alien or vampire ) to portray themselves and their condition, and to articulate their experiences in ways that were meaningful to them. Discussion: The findings of this study offer a unique contribution to knowledge by highlighting the fact that metaphors are essential to adolescents' narrations about living with, and communicating about, CKD experiences. Understanding how adolescents communicate about and experience their chronic condition is critical to enable health care providers to appreciate CKD beyond its physical and medical context; thereby providing awareness of the personal implications of chronic disease management on young people's psychological and social health and wellbeing. These finding have further implications for how health care providers might effectively communicate with adolescents about their personal experiences of living with CKD.